Geopolymer technology for the solidification of simulated ion exchange resins with radionuclides. (1st April 2019) - Lee, Wei-Hao; Cheng, Ta-Wui; Ding, Yung-Chin; Lin, Kae-Long; Tsao, Shih-Wei; Huang, Chun-Ping
Abstract: In this study, geopolymer was applied to convert ion exchange resins contaminated with radionuclides into a solid waste form. Geopolymer has superior properties to enable the encapsulation of spent resins. The allowable limit of resin content in the converted waste form was analyzed to evaluate the solidification capability of geopolymer. The encapsulation of ion exchange resins into solid waste form was conducted using geopolymer prepared with ground granulated blast furnace slag and alkaline solution in an ambient atmosphere, with the addition of wollastonite powder to adjust its mechanical properties. The physical and mechanical properties of the converted solid wastes prepared using different resin content ratios and various SiO2 /Na2 O molar ratios were tested. The results indicate the wet ion exchange resin (the moisture content in the resin is 51%) content and the compressive strength of the solid resin waste were measured as 45 wt% and 8.5 MPa, respectively. The morphology and mineral phases of the formed solid wastes were characterized using SEM and EDS. The mechanical performance test results proved the formed solid wastes could comply with the fuel cycle and material administration standards ruled by the Atomic Energy Council of Taiwan. These results suggest that this blast furnace slag-based geopolymer is a promising matrix material for the solidification of radioactive wastes. Highlights: GGBFS -based geopolymer is a promising matrix material for the solidification of radioactive wastes. The maximum solidified wet resin content can reach 45 wt% in GGBFS-based geopolymer systems. KMnO4 can be employed to pretreat the ion exchange resin in order to reduce resin shrinkage or swelling.